Digital map of zoo negara using geospatial information system (GIS) approach - Juarimi N.A.A.B.; Nasir N.R.M. (IOP Publishing Ltd, 2023)
Digital map; Geo-spatial information systems; Information medium; Large volumes; Malaysia; Mapping systems; Printed papers; Tourist attractions; Physics